The Dynamics of Quranic Translation in Indonesia: Analyzing the Relationship between Modern Islamic Movements and the Development of Tafsiriyah Translation - Haidar Edward Lumbantobing; Moh. Abdul Kholiq Hasan; Ainur Rhain; Kharis Nugroho; Andri Nirwana. AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the dynamics of Qur'an translation in Indonesia, focusing on the relationship between modern Islamic movements and the development of tafsiriyah translations. Through a case study of the work of Muhammad Thalib, the leader of the Indonesian Mujahidin Council (MMI), this article shows that Qur'an translation not only functions as a religious or linguistic activity, but is also used as a political and ideological tool to fight for the formalization of Islamic law in national life. This study uses a library study method with a discourse analysis approach to the translated texts of Thalib's tafsiriyah and MMI movement documents. The results reveal that Thalib's tafsiriyah translations, particularly his work entitled Al-Qur'anul Karim: Tarjamah Tafsiriyah, were developed as a corrective response to the official translation of the Ministry of Religious Affairs, as well as a medium for disseminating Islamist discourse that emphasizes the enforcement of sharia in its entirety, rejection of religious pluralism, and criticism of the democratic system. Analysis of several key verses shows that Thalib's interpretation tends to direct the meaning of the verses according to the movement's agenda, such as emphasizing male leadership (Q.S. an-Nisa: 34), the state's obligation to collect zakat (Q.S. at-Taubah: 103), and the integrity of the implementation of sharia (Q.S. Ali Imran: 103). Thus, this article concludes that the development of tafsiriyah translations in Indonesia cannot be separated from the socio-political context after the 1998 Reformation, where Islamic movements utilized freedom of expression to fight for their ideological visions through the medium of translating holy books.